TRANSFORMASI KURIKULUM MATEMATIKA DI NEW SOUTH WALES (NSW) EDUCATION STANDARDS AUTHORITY (NESA): ANALISIS FILOSOFIS, STRUKTURAL, DAN PEDAGOGIS BERDASARKAN DOKUMEN NESA K–12 - Saputra, Jusep; Mulyono; Waluya, Budi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
This study aims to analyze the transformation of the mathematics curriculum in New South Wales (NSW), Australia, developed by the New South Wales Education Standards Authority (NESA). A qualitative descriptive approach using document analysis was applied to examine the NESA K–12 mathematics syllabuses (2021–2024). The analysis covered four main dimensions: philosophical, structural, pedagogical, and evaluative. Findings reveal that the NESA mathematics curriculum reflects a humanistic-progressive philosophy, positioning mathematics as a means of logical and reflective reasoning through the Working Mathematically framework. The curriculum adopts a spiral and flexible structure, ensuring vertical continuity from Kindergarten to Stage 6 through differentiated pathways (Standard, Advanced, Life Skills, Extension 1–2, and Numeracy). Pedagogical implementation emphasizes inquiry-based, contextual, and technology-integrated learning, while the assessment system applies performance bands and evidence-based evaluation to ensure fairness and inclusivity. This model provides valuable insights for strengthening Indonesia’s Kurikulum Merdeka, fostering a reflective, inclusive, and competence-oriented mathematics education.